Locking the Coplanar Conformation of π‐Conjugated Molecules and Macromolecules Using Dynamic Noncovalent Bonds. Issue 2 (27th June 2017) - Zhu, Congzhi; Fang, Lei
Abstract: Torsional conformation of the backbone of a π‐conjugated molecule or macromolecule shapes its solubility, optoelectronic characteristics, rheological behaviors, and ultimately solid‐state functions. In order to tailor these molecular, supramolecular, and materials properties, the desired coplanar conformation in π‐conjugated systems can be locked by using dynamic noncovalent bonds. In this article, the syntheses, characterizations, and unique properties of conjugated molecules/polymers involving a variety of bridging noncovalent bonds are disussed in the context of coplanar backbone conformation. In addition, challenges in this specific field are identified and discussed for future breakthroughs in exploiting the promising potential of noncovalent‐bond‐bridged, π‐conjugated organic materials. Abstract : Backbone conformation plays a crucial role in shaping the properties of π‐conjugated molecules and macromolecules. The introduction of pre‐organized dynamic noncovalent interactions onto π‐conjugated systems enables active control on conformation, leading to tailored properties and functions.